A Review on Transport Phenomena Near the Critical Point of Fluids Under Weightlessness - Beysens, D. (Frontiers in Space Technologies, 2022)
Fluids near their liquid-vapor critical point, liquid mixtures near their miscibility critical point, exhibit universal behavior in their transport properties. Weightlessness is most often mandatory to properly evidence these properties. This review is concerned with some of the most important results obtained thanks to space experiments concerning thermal, mass, and momentum transport. Thermal aspects in pure fluids are mainly concerned with the discovery of a new thermalization process, the Piston Effect, leading to paradoxical effects such as a “critical speeding up” instead of the classical “critical slowing down”, heat seemingly flowing backwards and cooling resulting from heating. Mass transport deals with the process of phase transition when the fluid or the liquid mixture is thermally quenched from the homogeneous, supercritical region, to the two-phase region where it phase separates. Weightlessness makes universal the dynamics of phase separation. Momentum transport occurs when fluids are vibrated, leading to effects (interface position, instabilities) that resemble buoyancy effects seemingly caused by an artificial gravity. A number of still open questions is eventually given.